Kesanggupan memberi rasuah di kalangan pelajar universiti: kes kesalahan lalu lintas = Bribery amongst university students: Traffic offenses - Lim, Hock Eam; Tong, Tracy Pooi Yee; Woon, Moong Vooi (Universiti Kebangsaan Malaysia, 2009)
This paper studies the determinants of willingness to give bribe among university students, in case of traffic offence. Marginal benefit (time and money saved) that obtained in giving the bribe is the main determinants. This implies that, policy of anti-corruption by increase the fine is most likely to be ineffective. The finding of morality attachment is able to reduce the willingness to bribe, suggests that religious teaching should be the focus on anti-corruption eclucation. Students with high willingness to bribe are those who are male, Chinese CGPA more than 2.96 and low morality attachment. Anti-corruption education is suggested to focus on this group.